Esterification of Palm Fatty Acid Distillate Using Organophosphonic Acid-Functionalised Rice Husk Silica - Gaanty Pragas, Maniam; Mohd Hasbi, Ab. Rahim; M. M., Yusoff; Noor, Hindryawati; Shalizanis Mariyanti, Dora Siswanto (2015)
In the present study, renewable green fuel is produced using a by-product generated during the purification process of palm oil refinery, known as palm fatty acid distillate (PFAD). PFAD has been considered as the most promising biodiesel feedstock despite its drawbacks of high free fatty acid (FFA) and water content. In order to overcome these problems, the organophosphonic acid-functionalized rice husk silica (OP-RHS) catalyst was used in esterification of PFAD. Parametric study has been conducted and the optimal conditions were found to be: MeOH:oil molar ratio of 15:1 and 8 wt.% catalyst amount at 100 °C, yielding highest methyl ester content 88.6% at 8 h reaction time. The catalyst could maintain a high catalytic activity (> 80 %) even during the fourth cycles. The research results show that OP-RHS is a potential catalyst for biodiesel production using high FFA and moisture content feedstock.